Analysis of phase data from ground vibration measurements above a leaking plastic water pipe - Scussel, O. (2023)
One way to locate a buried plastic water pipe is to measure the surface vibration due to a leak in the region above the pipe, and to process the data to infer the pipe location. This paper investigates the physical mechanisms that propagate leak noise through the pipe and the surrounding soil to the ground surface. An analysis is carried out of the relative phase between vertical ground vibration measurements at points in a grid above the pipe. The study involves experimental measurements from a site in the UK with a more realistic leak mechanism compared to recent research, a simplified analytical model to gain insight into the underlying physics, and a numerical model to validate some of the assumptions made in the derivation of the analytical model. Three waves are principally involved in propagating leak noise to the ground surface from the pipe, namely the predominantly fluid-borne wave in the pipe, and the shear and compressional waves in the soil radiating from the pipe. Their influence on the ground surface vibration is investigated through measured and simulated phase contours over a rectangular grid of surface velocity measurements. It is shown how shear and compressional waves combine to affect the shape of the lines of constant phase on the ground. The results demonstrate the potential of the proposed analytical and numerical models to investigate wave radiation from buried water pipes, and possible pipe location strategies using phase data from surface vibration measurements.